An RNAi-based chemical genetic screen identifies three small-molecule inhibitors of the Wnt/wingless signaling pathway. - Gonsalves, F.C.; Klein, K.; Carson, B.B.; Katz, S.; Ekas, L.A.; Evans, S.; Nagourney, R.; Cardozo, T.; Brown, A.M.; DasGupta, R. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Misregulated ?-catenin responsive transcription (CRT) has been implicated in the genesis of various malignancies, including colorectal carcinomas, and it is a key therapeutic target in combating various cancers. Despite significant effort, successful clinical implementation of CRT inhibitory therapeutics remains a challenging goal. This is, in part, because of the challenge of identifying inhibitory compounds that specifically modulate the nuclear transcriptional activity of ?-catenin while not affecting its cytoskeletal function in stabilizing adherens junctions at the cell membrane. Here, we report an RNAi-based modifier screening strategy for the identification of CRT inhibitors. Our data provide support for the specificity of these inhibitory compounds in antagonizing the transcriptional function of nuclear ?-catenin. We show that these inhibitors efficiently block Wnt/?-catenin-induced target genes and phenotypes in various mammalian and cancer cell lines. Importantly, these Wnt inhibitors are specifically cytotoxic to human colon tumor biopsy cultures as well as colon cancer cell lines that exhibit deregulated Wnt signaling.